2011
DOI: 10.1021/bi200425b
|View full text |Cite
|
Sign up to set email alerts
|

Signals and Pathways Regulating Nucleolar Retention of Novel Putative Nucleolar GTPase NGP-1(GNL-2)

Abstract: NGP-1(GNL-2) is a putative GTPase, overexpressed in breast carcinoma and localized in the nucleolus. NGP-1 belongs to the MMR1-HSR1 family of large GTPases that are emerging as crucial coordinators of signaling cascades in different cellular compartments. The members of this family share very closely related G-domains, but the signals and pathways regulating their subcellular localization and their functional relevance remain unknown. To improve our understanding of the nuclear transport mechanism of NGP-1, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…Studies using zebrafish showed p53 stabilization upon Ngp-1 depletion (17) and also suggested its role in ribosome biogenesis (18). Previous studies from our laboratory showed that increased NGP-1 expression in human neural precursor cells compared with differentiated astrocytes (16). Furthermore, NGP-1 levels were up-regulated in mitogeninduced human peripheral blood mononuclear cells (16), suggesting its association with cell proliferation.…”
Section: Pathwaymentioning
confidence: 77%
See 4 more Smart Citations
“…Studies using zebrafish showed p53 stabilization upon Ngp-1 depletion (17) and also suggested its role in ribosome biogenesis (18). Previous studies from our laboratory showed that increased NGP-1 expression in human neural precursor cells compared with differentiated astrocytes (16). Furthermore, NGP-1 levels were up-regulated in mitogeninduced human peripheral blood mononuclear cells (16), suggesting its association with cell proliferation.…”
Section: Pathwaymentioning
confidence: 77%
“…Previous studies from our laboratory showed that increased NGP-1 expression in human neural precursor cells compared with differentiated astrocytes (16). Furthermore, NGP-1 levels were up-regulated in mitogeninduced human peripheral blood mononuclear cells (16), suggesting its association with cell proliferation. Nevertheless, the mechanism by which NGP-1 modulates cell proliferation remains unexplored.…”
Section: Pathwaymentioning
confidence: 77%
See 3 more Smart Citations